RGS14414 treatment induces memory enhancement and rescues episodic memory deficits. - Masmudi-Martín, Mariam; Navarro-Lobato, Irene; López-Aranda, Manuel Francisco; Delgado, Gloria; Martín-Montañez, Elisa; Quirós-Ortega, María Elena; Carretero-Rey, Marta; Narváez, Lucía; García-Garrido, María F.; Posadas, Sinforiano; López-Téllez, Juan Félix; Blanco, Eduardo; et al. (Wiley, 2019)
Memory deficits affect a large proportion of the human population and are associated with aging and many neurologic, neurodegenerative, and psychiatric diseases. Treatment of this mental disorder has been disappointing because all potential candidates studied thus far have failed to produce consistent effects across various types of memory and have shown limited to no effects on memory deficits. Here, we show that the promotion of neuronal arborization through the expression of the regulator of G-protein signaling 14 of 414 amino acids (RGS14414) not only induced robust enhancement of multiple types of memory but was also sufficient for the recovery of recognition, spatial, and temporal memory, which are kinds of episodic memory that are primarily affected in patients or individuals with memory dysfunction. We observed that a surge in neuronal arborization was mediated by up-regulation of brain-derived neurotrophic factor (BDNF) signaling and that the deletion of BDNF abrogated both neuronal arborization activation and memory enhancement. The activation of BDNF-dependent neuronal arborization generated almost 2-fold increases in synapse numbers in dendrites of pyramidal neurons and in neurites of nonpyramidal neurons. This increase in synaptic connections might have evoked reorganization within neuronal circuits and eventually supported an increase in the activity of such circuits. Thus, in addition to showing the potential of RGS14414 for rescuing memory deficits, our results suggest that a boost in circuit activity could facilitate memory enhancement and the reversal of memory deficits.
Keywords: Memoria - Aspectos fisiológicos; Procesos cognitivos; Neurotrofinas; Neurociencias; Enfermedades neurodegenerativas - Tratamiento; Cognitive dysfunction; BDNF; Memory circuit activation; Recovery of memory functions; Behavioral performance